Sustain ability Assessment and Land Use Priority in an Arid Region: A Case Study - Hassanli, A M (Annals of Arid Zone, 2016)
To assess the sustainability and to determine the land use priority of the main irrigated crops in Darab (south-east of Iran), an arid region with water scarcity, growing com, cotton, wheat and citrus was selected for evaluation as a case study. Seven sustainable indices; water use efficiency, water requirement, economic return, soil erosion, environmental impacts, compatibility to new irrigation systems and labor requirements were used to evaluate the agricultural sustainability and sustainable land use. The effects of cultivation and lana use on the sustainable indices were examined. The indices were given a score based on variation increment. Each crop finally received a weight corresponding to the sustainable indices. The results showed that citrus received the highest score of 29, com a score of 8, wheat a score of 7 and cotton received the lowest score of 3. This study could be an introduction to develop a mathematical model for sustainable land use of the irrigated crops in the region with water scarcity. However, the conclusions of. this study cannot be generalized.